Integrasi Model Pembangkit Listrik Tenaga Angin Pada Analisis Aliran Daya Sistem Tenaga - Rudy Gianto (Universitas Syiah Kuala, 2020)
This paper proposes a new method for modeling and integrating wind turbine generating system (WTGS) into power flow analysis. The proposed WTGS model is based on the slip calculation of the WTGS induction generator. Unlike some previous methods where machine slip is determined after the iteration process has been completed, in the proposed method, machine slip is included in the calculation or iteration process and computed together with other electrical quantities. In this way, the formulation for induction generator rotor voltage (which isusually complicated and often represented by bi-quadratic equation) is no longer needed in the modeling. Validation results show that the proposed method is accurate. The application of the WTGS model in load flow analysis of the multi-bus electric power system is also presented. In addition, the effect of WTGS installation on system steady-state performance is also investigated in this paper.